The impact of adoption of power factor correction technology on electricity peak demand in Uganda - Geofrey Okoboi; Joseph Mawejje (Journal of Economic Structures, 2016)
This paper examines the impact of adoption of power factor correction technology on electricity peak demand in Uganda. Specifically, the paper examines the variability of peak electricity demand in the periods before and after the implementation of power factor improvement schemes and assesses the likely impact of power factor improvement schemes on peak demand. Results suggest that power factor correction technology implemented among industries and commercial enterprises increased the power factor in these industries from an average of 0.68 to 0.95 and saved up to 8.04 MVA of demand as at the end of 2014. Results further indicate that the implementation of the power factor correction scheme has reduced the growth rate and abated the variability of both total maximum/peak demand and domestic peak demand. Finally, with the implementation of power factor correction scheme, there is a noticeable reduction in electricity consumption at peak time of use (TOU) and growth in consumption of electricity at nonpeak time TOU, which was not the case before the implementation of the scheme.
Keywords: 330